(untitled) (Texas Journal of Philology, Culture and History, 2023)
This article defines using sewing terms in proverbs. It includes some proverbs containing sewing terms and analyze their functions. The linguocultural aspect of sewing terms in proverbs provides a glimpse into the interplay between language, culture, and the craft of sewing. These proverbs contain valuable lessons and insights, drawing upon sewing terminology to convey wisdom